SACRALIZATION OF PANCASILA: IDEOLOGY AND REPRESSION IN THE IMPLEMENTATION OF THE PANCASILA IDEOLOGY DEVELOPMENT BOARD (BPIP) AND GUIDELINES FOR THE APPRECIATION AND PRACTICE OF PANCASILA (P4) - Mustapa, Hasan; Zulkarnaen, Nanang; Feny Yuniarti, Putri (Universitas Negeri Semarang, 2024)
Pancasila's role has become an unavoidable topic of dispute. For intellectuals, Pancasila should be an open ideology. The authorities frequently make Pancasila a closed doctrine. Ideology becomes closed when it is officially implemented by the state and interpreted unilaterally to assess incompatibility with societal interpretations. This qualitative study compares New Order government policies to the Guidelines for the Appreciation and Practice of Pancasila (P4) project run by the Pancasila Ideology Development Agency (BPIP). Various journal papers were collected, evaluated, and seen through the lens of ideology and repression. According to the research findings, when Pancasila was institutionalized, such as during the New Order period, it was frequently employed as a beating stick for parties that disagreed with the government's political goals. This potential can also be observed in BPIP during Joko Widodo's tenure, if executed strictly. Pancasila is founded on the principle of openness, which was echoed by the Founding Fathers. Often told behind closed doors using a frozen sacralization procedure.